Potret Peningkatan Kesehatan Lingkungan Untuk Pencegahan Penyakit Berbasis Lingkungan di Desa Ngayub Kabupaten Maluku Tenggara - Wa Rina; Agnes Batmomolin; Jonathan Kelabora (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Until now, environmental-based diseases (EBD) are still a danger to the community, including respiratory tract infection (RTI) and diarrhea. RTI and diarrhea can be experienced by anyone, from infants to adults. Other diseases caused by the environment, namely, malaria, chikungunya, dengue fever, filariasis and so on. The purpose of this community service activity is to increase public awareness in Ngayub Village, Manyeuw District, Southeast Maluku Regency about the importance of maintaining a clean environment and clean and healthy living behavior (PHBS), through counseling and social services. The methods used in implementing community service are Focus Group Discussion (FGD), counseling, and community service as well as planting protected trees. The results of community service activities regarding FGDs found that people still throw garbage everywhere, as many as 70% of houses do not have sewerage (SPAL), there is a lack of clean water sources so that people have to buy clean water through water tanks and collect rainwater for used as clean water to meet daily needs. Lack of clean water sources, littering everywhere, and no SPAL in every house can cause environmental-based diseases. So the community service team provided counseling on the importance of keeping the environment clean to prevent PBL which was attended by 85% of the community, joint community service and planting of protected trees attended by 85% of the people of Ngayub Village.